Estudos estruturais e magnéticos de oxiboratos anidros de cobalto dos tipos ludwigita e hulsita - Freitas, Daniele Cristina Silva de (2011)
This work reports the study of four ludwigite-type oxyborates: Co3O2BO3, Co2FeO2BO3, Ni2FeO2BO3 e Co5Ti(O2BO3)2 and a fifth of the hulsite-type: Co5.52Sb0.48(O2BO3)2. We have carried-out the synthesis of these materials as well as temperature dependent measurements of X-ray diffraction in single crystals, ac magnetic susceptibility, dc magnetization and specific heat. The main results are reported below. 1 - Homometallic ludwigite Co3O2BO3: the main goal of this study was to compare the properties of this ludwigite with those of the only other known homometallic ludwigite: Fe3O2BO3. We have found that the cobalt ludwigite presents only one magnetic transition temperature and no structural transition unlike Fe3O2BO3. 2 - Ludwigites Co2FeO2BO3 e Ni2FeO2BO3: in both of them the ions Fe3+ order around 110 K as in the iron homometallic ludwigite. The ludwigite Ni2FeO2BO3 shows antiferromagnetism below 42 K. In the ludwigite Co2FeO2BO3 there is spin freezing at 70 K with reentrant ferrimagnetism under applied field and antiferromagnetism along the c axis. 3 - Ludwigite Co5Ti(O2BO3)2: this ludwigite was synthesized for the first time during this work. It shows spin freezing at 27 K with ferrimagnetism under applied field and an easy magnetization direction orthogonal to the c axis. 4 - Hulsite Co5.52Sb0.48(O2BO3)2: this hulsite [17] was also synthesized for thr fifirst time during this work. This material exhibits magnetic ordering below 43 K and a magnetization curve similar to that of the cobalt homometallic ludwigite. At low temperatures the specific heat displays a T2 dependence with temperature which indicates, as expected, the presence of two-dimensional magnons in this system. Preliminary studies with synthetic iron hulsite have been carried out and are reported in the Apendix A.